Encyclopedia of Life Support Systems (EOLSS) - Cock, I. E. (Pharmacognosy Communications)
The Encyclopedia of Life Support Systems (EOLSS) (http://www.eolss.net/) is an integrated multidisciplinary online encyclopedia that is written and edited by leading researchers in their fields. EOLSS is a joint project in conjunction with the United Nations Educational, Scientific and Cultural Organisation (UNESCO). It is aimed at promoting health, global maintainance and all aspects of sustainable development, covering diverse themes including ecological issues, bio-innovation, sustainable production and biosecurity. All volumes are invited, with thousands of contributions from leading scholars from over 100 countries worldwide, making the EOLSS possibly the largest and most ambitious data base of its kind. The encyclopedias are designed as a useful reference guide for a wide range of users, from students beginning studies of the subject matter, through to experienced researchers and policy makers.